2021
DOI: 10.3390/nu13062035
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Melatonin and Glycine Decrease Tumor Growth through Antiangiogenic Activity in Experimental Colorectal Liver Metastasis

Abstract: Despite multimodal treatment strategies, clinical outcomes of advanced stage colorectal cancer (CRC) patients remain poor. Neoadjuvant/adjuvant chemotherapy efficacy is limited due to chemoresistance, toxicity, and negative side effects. Since both melatonin and glycine have anti-cancer activities without relevant side effects, this study was designed to investigate their combined effects in experimental CRC liver metastases. CRC metastasis with CC531 cells were induced in male Wistar rats. Melatonin and glyci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…Two hours prior to IRI or sham procedure, the melatonin and combined treatment groups received 1.5 mL of milk (3.5% fat) containing 50 mg/kg melatonin (Sigma-Aldrich, St. Louis, MO, USA) via gavage, while the control and glycine groups received the same type of milk containing a corresponding amount of microcrystalline cellulose (placebo; from Sigma-Aldrich, St. Louis, MO, USA). The administration route and dose of both investigated substances (melatonin and glycine) were adopted based on previous experiments [27,28,40,44,53,54]. Water consumption, food intake and body weight were recorded regularly (for details, see Figure 5).…”
Section: Animal Groups and Experimental Designmentioning
confidence: 99%
“…Two hours prior to IRI or sham procedure, the melatonin and combined treatment groups received 1.5 mL of milk (3.5% fat) containing 50 mg/kg melatonin (Sigma-Aldrich, St. Louis, MO, USA) via gavage, while the control and glycine groups received the same type of milk containing a corresponding amount of microcrystalline cellulose (placebo; from Sigma-Aldrich, St. Louis, MO, USA). The administration route and dose of both investigated substances (melatonin and glycine) were adopted based on previous experiments [27,28,40,44,53,54]. Water consumption, food intake and body weight were recorded regularly (for details, see Figure 5).…”
Section: Animal Groups and Experimental Designmentioning
confidence: 99%
“…For several years our study group has been investigating different cancer-suppressing agents in an orthotopic CRCLM rat model. We have previously determined that both glycine and melatonin substantially suppress CRCLM growth in vivo [ 29 , 30 ]. Currently, we are conducting a similar study looking into possible combinations of these novel tumor-suppressing agents and their possible synergistic effects.…”
Section: Discussionmentioning
confidence: 99%
“…The FOLFOX CTx regimen was chosen in this experiment due to its proven potency in treating CRCLM [ 32 , 33 ]. This regimen was also used in another similar study by our research group with the desired tumor suppressive effect [ 29 , 30 ]. On day 28 a mixture of 100 mg/m 2 Calcium folinate (Sandoz, Holzkirchen, Germany), 42.5 mg/m 2 Oxaliplatin (Fresenius Kabi, Bad Homburg, Germany) and 500 mg/m 2 5-Fluoruracil (Sandoz, Holzkirchen, Germany) was used.…”
Section: Methodsmentioning
confidence: 99%
“…Collin et al confirmed that menadione plus melatonin on Caco-2 cells could reduce cell proliferation, induce reactive nitrogen species formation, enhance superoxide anion content, and increase catalase activity, suggesting the potential as adjuvant therapy for CRC acting on different oncogenic pathways (85). Kvietkauskas et al designed a study to explore the combined role of melatonin and glycine in CRC liver metastasis (86). They found that supplementation with melatonin and glycine reduce CRC liver metastasis growth by acting as natural antiangiogenic molecules.…”
Section: The Role Of Melatonin In Colorectal Cancermentioning
confidence: 99%
“…Kvietkauskas et al. designed a study to explore the combined role of melatonin and glycine in CRC liver metastasis ( 86 ). They found that supplementation with melatonin and glycine reduce CRC liver metastasis growth by acting as natural antiangiogenic molecules.…”
Section: The Role Of Melatonin In Gi Cancermentioning
confidence: 99%